Use of amniotic membrane in trabeculectomy for the treatment of glaucoma: a pilot study - Eliezer,Ricardo Nunes (2006)
PURPOSE: To compare the safety and efficacy of human preserved amniotic membrane (AM) in the trabeculectomy for treatment of primary open-angle glaucoma. METHODS: A prospective, randomized clinical trial compared primary trabeculectomy with amniotic membrane (study group) and without amniotic membrane (control group) in the treatment of the glaucoma. Intraocular pressure (IOP), number of glaucoma medications and appearance of the bleb were compared between the two groups. Thirty-two patients divided into two groups of 16 patients were followed for a period of 12 months. RESULTS: The difference of the mean postoperative intraocular pressure between groups was not statistically significant (15.19 ± 3.33 in the control group and 12.81 ± 2.48 in the study group p=0.297) at one year follow-up. Postoperative number of medications decreased in both groups (p<0.001and p=0.007, study group and control respectively). At the end of a 12-month follow-up period, nine eyes (56.25%) showed thin, avascular blebs in the study group as compared to only one eye (6.25%) in the control group. CONCLUSIONS: Trabeculectomy with amniotic membrane and standard trabeculectomy promote lower postoperative intraocular pressure although results showed no statistically significant difference between groups regarding postoperative intraocular pressure after one year follow-up.